2022
DOI: 10.3389/fnins.2022.799739
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory α-Melanocyte-Stimulating Hormone Protects Retina After Ischemia/Reperfusion Injury in Type I Diabetes

Abstract: Retinal ischemia/reperfusion (I/R) injury is a major cause of vision loss in many ocular diseases. Retinal I/R injury is common in diabetic retinopathy, which as a result of hyperglycemia damages the retina and can cause blindness if left untreated. Inflammation is a major contributing factor in the pathogenesis of I/R injury. α-Melanocyte-stimulating hormone (α-MSH) is an anti-inflammatory peptide hormone that has displayed protective effects against I/R-induced organ damages. Here, we aimed to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
2
8
0
Order By: Relevance
“…Treatment of diabetic rodent models with α-MSH suppresses the retinopathy and also suppresses the extent of retinal damage caused by central vein occlusion in diabetic stroke mice models [21,24,25,43]. The actions of α-MSH are not restricted to diabetic conditions and are mostly on the cellular response to injury and inflammation [14,15,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of diabetic rodent models with α-MSH suppresses the retinopathy and also suppresses the extent of retinal damage caused by central vein occlusion in diabetic stroke mice models [21,24,25,43]. The actions of α-MSH are not restricted to diabetic conditions and are mostly on the cellular response to injury and inflammation [14,15,17].…”
Section: Discussionmentioning
confidence: 99%
“…The neuropeptide suppresses the migration and infiltration of polymorphonuclear leukocytes into the anterior chamber of eyes with endotoxin-induced uveitis [45,46]. In diabetic mice, α-MSH treatment suppresses the pathology of diabetic retinopathy by promoting the survival of both ganglion cells and photoreceptors, with the retention of the bloodocular barrier and the inhibition of the induction of neovascularization [21,24,25,43]. The loss of photoreceptors in RCS rat retinas is retained with α-MSH treatment [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, α-MSH treatment may signal retinal cell survival or inhibit apoptosis signals [ 6 , 18 , 33 , 35 , 36 ]. It has been demonstrated that using α-MSH as a treatment protects the retina from degeneration caused by EAU, diabetic retinopathy, and ischemia/reperfusion [ 18 , 19 , 21 , 26 , 37 , 38 , 39 , 40 ]. While experimentally using α-MSH has demonstrated benefits, α-MSH is a highly unstable molecule [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of EAU by PL-8331-treatment showed that by activating the melanocortin-signaling pathways, there was the suppression of inflammation and preservation of retinal structure similar to what others have seen using native α-MSH [ 16 , 19 , 43 , 44 , 45 ]. The literature describes the potential of stimulating the melanocortin signaling pathways to promote the survival of retinal cells [ 19 , 27 , 33 , 37 , 43 , 46 , 47 , 48 ]. The histology of the EAU retinas showed that PL-8331 treatment observably protects the photoreceptor layer.…”
Section: Discussionmentioning
confidence: 99%